2014
DOI: 10.1051/e3sconf/20140301019
|View full text |Cite
|
Sign up to set email alerts
|

Contractor’s Awareness on Occupational Safety and Health (OSH) Management Systems in Construction Industry

Abstract: Abstract. Occupational Health and Safety Management Systems is part of the overall management system that facilitates the management of the OS&H risks associated with the business of the organization. This includes the organizational structure, planning activities, responsibilities, practices, procedures, processes and resources for developing, implementing, achieving, reviewing and maintaining the organization's OS&H policy. The purpose of this research is to determine the level of awareness of contractors on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The findings of Mohd-Kamar, et al (2014) is supported by this section's results. Student quantity surveyors, just like the firms in Mohd-Karmar, et al's (2014) study, are aware of the importance of construction H&S, what is lacking is their understanding of the roles of quantity surveyors in the management of construction H&S. Muiruri and Mulinge (2014) recommended that massive education campaigns be launched to arouse awareness among all parties with direct or indirect bearing on accidents occurrence and their prevention.…”
Section: Importance Of Effective Construction Hands Managementsupporting
confidence: 81%
See 2 more Smart Citations
“…The findings of Mohd-Kamar, et al (2014) is supported by this section's results. Student quantity surveyors, just like the firms in Mohd-Karmar, et al's (2014) study, are aware of the importance of construction H&S, what is lacking is their understanding of the roles of quantity surveyors in the management of construction H&S. Muiruri and Mulinge (2014) recommended that massive education campaigns be launched to arouse awareness among all parties with direct or indirect bearing on accidents occurrence and their prevention.…”
Section: Importance Of Effective Construction Hands Managementsupporting
confidence: 81%
“…Clearly, the result shows that the students are not aware of QS's roles in construction H&S. This is related to the non-inclusion of construction H&S as a separate module in their curriculum. -Kamar et al (2014) found the level of awareness of construction H&S to be high for class A contractors in Kelantan, Malaysia. This is not supported by the present study.…”
Section: Awareness Of Quantity Surveyors' Hands Roles In Construction Hmentioning
confidence: 93%
See 1 more Smart Citation
“…Kumar & Bansal [40] stated that effective safety knowledge among construction professionals reduces accidents and directly or indirectly reduces project cost. The above view is supported by Kamar et al [41]. However, Sunindijo and Zou [42] suggested that employees, including project personnel, should be equipped with safety skills and with necessary H&S knowledge to enable them to work safely and to encourage others to do the same.…”
Section: Knowledge Of Health and Safety Informationmentioning
confidence: 99%
“…OHSMS includes the organizational structure, planning activities, responsibilities, practices, procedures, processes and resources for developing, implementing, achieving, reviewing and maintaining the organization's OHS policy. Safety management system is performance oriented as opposed to compliance oriented (Mohd Kamar et al, 2014). It is generally felt that safety practitioners encounter difficulties in dealing with the safety management issues.…”
Section: Literature Reviewmentioning
confidence: 99%